PWE-108 Staining and dysplasia status in barrett's oesophagus; a retrospective study. (17th June 2017) - Corovic, A; Miremadi, A; Fitzgerald, RC
Abstract : Introduction: p53 immuno-staining may be a useful adjunct in the histopathological assessment of dysplasia status in Barrett's Oesophagus. In particular, a "significant" or "non-significant" pattern of p53 staining may be a discriminating feature in cases that are otherwise "indefinite for dysplasia", potentially helping to up- or down-stage these difficult cases so as to facilitate further management. Method: We conducted a retrospective analysis of p53 staining practice and histopathological outcome (dysplasia state) for oesophageal biopsies taken over a four-year period between 2009 and 2013 at one major UK hospital. Results: A total of 486 oesophageal biopsies were identified that had p53 staining undertaken between 2009 and 2013. Sizeable numbers of cases were stained from 2011 onwards, with the number stained increasing annually from that year over the time period considered. In parallel with this increase in p53 staining practice, we observed a decrease in the proportion of cases classed as indefinite for dysplasia; from 26.8 % of those stained in 2011, to 18.4 % by 2013. The fall in the proportion of indefinite cases was accompanied by a rise in the proportion of cases classed as showing no dysplasia (from 21.1 % in 2011 to 50.7 % in 2013), and a fall in the proportion of cases classed as showing dysplasia (from 35.2 % to 20.2 % for low-grade; 12.7 % to 5.9 % for high-grade), over the same time period. p53 staining outcome also appeared to correlate well with final dysplasia status. Namely, 91 % of those cases without dysplasia for which p53 staining outcome was documented had a non-significant pattern of p53 staining, and 85.3 % of those cases with low-grade dysplasia and above had a significant pattern of p53 staining. Conclusion: p53 staining would appear to be a useful adjunct to the standard evaluation of dysplasia status in Barrett's Oesophagus and may help to reduce the number of "indefinite for dysplasia" cases that would otherwise mandate unnecessary follow-up endoscopies. Further studies with a prospective design would be required to further support this conclusion. Disclosure of Interest: None Declared